Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Terbimbing Pada Materi Laju Reaksi Di SMA Indonesia Muda - Laurelia Lusiana; Eny Enawaty; Rahmat Rasmawan (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
This study aims to determine the feasibility of student worksheet media based on guided inquiry on the reaction rate material and to describe the chemistry teacher's response to the developed student worksheets. This research is a research and development (R&D) using the 4-D model which is limited to the develop stage. The subject of this research is the response to 3 teachers who teach chemistry lessons in SMA. The instruments in this study were the feasibility assessment sheet and the teacher response assessment sheet. The results of data processing showed that the student worksheets media obtained material feasibility of 91.67%, language feasibility of 90.62%, and graphic feasibility of 93.75% with very feasible categories. the results of the calculation of the percentage of teacher response questionnaires of 89.39% with the high category. This shows that the teacher's response to the student worksheets media is very high. so that the LKPD media can be used as a complementary teaching material on the reaction rate material.